High frequency of JAK2 exon 12 mutations in Korean patients with polycythaemia vera: novel mutations and clinical significance. Issue 8 (19th May 2016) - Park, Chang-Hun; Lee, Ki-O; Jang, Jun-Ho; Jung, Chul Won; Kim, Jong-Won; Kim, Sun-Hee; Kim, Hee-Jin
Abstract : Gain-of-function mutations in JAK2 are the molecular hallmarks of polycythaemia vera (PV), one of the myeloproliferative neoplasms. Most (∼95%) patients harbour V617F mutation in exon 15, while the rest have small insertion/deletion mutations in exon 12. We investigated JAK2 mutations in 42 Korean patients with PV. V617F was detected by sequencing and allele-specific PCR. When V617F was negative, sequencing and fragment length analyses were performed to detect exon 12 mutations. As a result, all patients had JAK2 mutations: 37 (88%) harboured V617F, and 5 (12%) had exon 12 mutations. Two patients had novel exon 12 mutations (H538_R541delinsLII and F537_K539delinsVL). Genotype–phenotype correlations demonstrated lower white blood cell and platelet counts in exon 12 mutations than V617F. The frequency of JAK2 exon 12 mutations was higher than expected in Korean patients with PV. Molecular genetic testing for JAK2 exon 12 mutations is mandatory for diagnosis and genotype–phenotype correlations in patients with erythrocytosis and suspected PV.